ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK HOTEL DI KOTA SEMARANG - Rifqy Sabatini; Evi Yulia Purwanti (Universitas Diponegoro, 2013)
Local autonomy is the important moment for the local area to holds their own government. The local area is given the trust to regulate their own household. Tax is one of main goverment’s revenue to finance all the needs of region. The large and potentital one of tax revenue in Semarang is Hotel tax revenue.The aim of this research is to analyzed effect of the number of room occupants and tourists, average tariff per room, also PDRB that become the factors determining hotel tax revenue in Semarang.The analysis based on the regression by using method of least square analysis (Ordinary Least Square) and the research was a descriptive study. The data used are secondary data during the years 1996-2010 obtained from the Badan Pusat Statistik (BPS) of Central Java Province and Semarang City, DPKAD of Semarang City, and Dinas Kebudayaan dan Pariwisata of Central Java Province.Based on the analysis results, the number of room occupants and average tariff per room is significant at α = 5 percent on hotel tax revenue, on the other hand, PDRB and the number of tourists not have a significant influence. Adjusted R-Square value of 0,504 which mean 50,4 percent of hotel tax revenue variation can be explain from four variation of independent variabels.